IMPLEMENTASI MANAJEMEN PENGETAHUAN PADA SISTEM PENGELOLAAN IJAZAH DI UPBJJ-UT BOGOR - Marta Dhewi, Ratna (Jurnal Organisasi Dan Manajemen, 2012)
This research aimed to examine the pattern of managing document certification at Bogor regional office for the last decade, furthermore, to design the digital model which offers insights into what is required to strategically align transcript management practice at Bogor regional office. The research was conducted by purposive sampling at Bogor Regional office considering that it represents the complexity of the organization that involves only a few employees with varying computational competencies and various task capabilities. However, they have been able to implement the knowledge management systems in providing services to customers. The data of this research were primary data. Data analysis were conducted based on an ongoing basis, with the following steps: preparation of the theme of data, classification and mapping of data based on a theme that has been set up, compilation, reduction, data cleaning, incorporation into the theme of the final data, triangulation of data, and data interpretation. This research discovered that managing certification documents of graduation at Bogor regional proved to be continuously updated and improved by the management team, and supported by top level management. The finding of this research proposed that the web based digital model of the certification documents management system (from acceptance, storage to distribution) is the most suitable model to be implemented at the regional offices.   Penelitian ini bertujuan mendeskripsikan pola pengelolaan dokumen sertifikasi di UPBJJ-UT Bogor selama sepuluh tahun terakhir dan menemukan model digital yang paling tepat untuk pengelolaan ijazah/transkrip yang efisien di UPBJJ-UT Bogor. Penelitian ini dilakukan dari bulan Maret sampai November 2011. Pemilihan lokasi penelitian dilakukan dengan cara purposive sampling dengan mempertimbangkan bahwa UPBJJ UT Bogor dapat mewakili kompleksitas organisasi yang melibatkan hanya beberapa pegawai dengan penguasaan komputer yang minim, namun telah mampu menerapkan sistem manajemen pengetahuan dalam memberikan pelayanan kepada pelanggannya. Data penelitian ini menggunakan data primer. Analisis data dilakukan berdasarkan secara berkelanjutan, dengan langkah-langkah berikut: persiapan tema data, klasifikasi dan pemetaan data didasarkan pada tema yang telah diatur, kompilasi, reduksi, pembersihan data, penggabungan ke dalam tema data akhir, triangulasi data, dan interpretasi data. Hasil penelitian ini menyatakan bahwa penanganan dokumen sertifikasi di UPBJJ-UT Bogor terbukti terus mengalami perbaikan dan mendapat dukungan yang baik dari staf dan kepemimpinan. Web base model menjadi model yang paling cocok untuk diimplementasikan di kantor UPBJJ